2009
DOI: 10.1007/s00425-009-0919-1
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur deprivation limits Fe-deficiency responses in tomato plants

Abstract: The aim of this work was to clarify the role of S supply in the development of the response to Fe depletion in Strategy I plants. In S-sufficient plants, Fe-deficiency caused an increase in the Fe(III)-chelate reductase activity, 59Fe uptake rate and ethylene production at root level. This response was associated with increased expression of LeFRO1 [Fe(III)-chelate reductase] and LeIRT1 (Fe2+ transporter) genes. Instead, when S-deficient plants were transferred to a Fe-free solution, no induction of Fe(III)-ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
99
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(123 citation statements)
references
References 37 publications
(41 reference statements)
20
99
3
Order By: Relevance
“…In the last 10 years, increased ethylene production by roots and/or shoots has been described for other nutrient deficiencies, such as K (Shin and Schachtman, 2004;Benlloch-Gonz谩lez et al, 2010), S (Zuchi et al, 2009;Moniuszko et al, 2013), N (Zheng et al, 2013), and Mg (Hermans et al, 2010). The higher ethylene production described for nutrient deficiencies has been further supported by results showing up-regulation of genes implicated in ethylene synthesis.…”
supporting
confidence: 66%
“…In the last 10 years, increased ethylene production by roots and/or shoots has been described for other nutrient deficiencies, such as K (Shin and Schachtman, 2004;Benlloch-Gonz谩lez et al, 2010), S (Zuchi et al, 2009;Moniuszko et al, 2013), N (Zheng et al, 2013), and Mg (Hermans et al, 2010). The higher ethylene production described for nutrient deficiencies has been further supported by results showing up-regulation of genes implicated in ethylene synthesis.…”
supporting
confidence: 66%
“…We propose from our results that inactive and active FIT proteins are not stable inside cells and can be degraded, indicated by arrows pointing to ellipses with light gray-white shading. Fe deficiency leads to ethylene production (Romera et al, 1999;Zuchi et al, 2009). EIN3/ EIL1 activated in the ethylene signaling pathway physically interact with FIT, which inhibits proteasomal degradation of FIT (EIN3/EIL1 are represented as dark-gray ellipses; FIT binding to EIN3/EIL1 does not involve the bHLH domain of FIT).…”
Section: Explanation For the Physiological Effects Of Ein3/eil1 Actiomentioning
confidence: 99%
“…Experiments with the plant hormone ethylene in different dicot plants indicated a physiological connection between ethylene and iron deficiency signaling. Ethylene is produced upon Fe deficiency (Romera et al, 1999;Zuchi et al, 2009). Applying ethylene precursors such as 1-aminocyclopropane-1-carboxylic acid or ethephon to plants could mimic morphological growth responses of Fe-deficient plants (Romera and Alcantara, 1994;Schmidt et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Zuchi et al (2009) showed that, in tomato plants exposed to both S and Fe starvation, no induction of Fe(III)-chelate reductase activity and ethylene production occurred. Thus, S deficiency seems to prevent the development of the typical responses to Fe deficiency in tomato.…”
mentioning
confidence: 99%
“…Recently, it was shown that the iron (Fe) use efficiency in maize (Zea mays; Astolfi et al, 2003;Bouranis et al, 2003), barley (Hordeum vulgare; Kuwajima and Kawai, 1997;Astolfi et al, 2006a), tomato (Solanum lycopersicum; Zuchi et al, 2009), and durum wheat (Triticum durum; Zuchi et al, 2012;Ciaffi et al, 2013) increased under adequate S supply. In these studies, it has been suggested that, in grasses (strategy II plants), this effect could be ascribed to a decrease in the production and release of phytosiderophores induced by S deficiency, whereas in tomato (a strategy I plant), the effect was rather caused by an impaired ethylene and nicotianamine (NA) production.…”
mentioning
confidence: 99%